Literature Review : Efektivitas Perawatan Luka dengan Madu pada Luka Ulkus Diabetikum - Wulan Yulianti, Ajeng; Aini, Nurul; Kulsum, Umi; Hendrayani, Pajar; Nurhasanah, Cucu; Susanto, Adi Dwi (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Diabetes mellitus, commonly known as diabetes, is a metabolic disorder caused by the pancreas not producing enough insulin or the body being unable to use the insulin produced effectively, leading to hyperglycemia beyond normal limits. Various complications can arise from diabetes mellitus, one of which is diabetic ulcers. One therapy for treating diabetic ulcers is honey, which has been proven to have many benefits, including anti- inflammatory and antibacterial properties, as well as accelerating the granulation and epithelialization processes. This study aims to assess the effectiveness of honey in treating diabetic ulcers through a journal review. The research method used was a literature review, with journal searches conducted in the PubMed, Research Gate, and Google Scholar databases. Inclusion criteria were studies published between 2015 and 2025, in either Indonesian or English. Data were analyzed using a narrative synthesis approach, comparing results across studies. A review of 10 articles showed that honey contains antimicrobial and anti-inflammatory properties, acts as a moisturizer at the wound base, has an osmotic effect, reduces edema in wound cells, accelerates angiogenesis and granulation in wounds, accelerates collagenase and epithelialization in wounds, enhances lymphocyte and phagocyte activity, and accelerates debridement of necrotic tissue. Some studies compared the use of dry dressings with the use of honey. Additionally, research indicated factors influencing healing time, such as wound condition, treatment duration, and respondent age. Honey contains numerous beneficial compounds proven effective in accelerating the healing of diabetic ulcers